How Does Employees’ Narcissism Influence Organizational Commitment? The Role of Perceived Supervisor Support and Abusive Supervision - Yu, Boxiang; Meng, Yong; Li, Chaoping; Liu, Dege (Frontiers in Psychology, 2022)
Narcissism has an important influence on employees’ attitudes and behavior. However, research on the mechanism of this process is still relatively scarce. Based on the conservation of resources theory, we constructed a conceptual model of the relationship between narcissism and organizational commitment and explored the role of perceived supervisor support and abusive supervision in this process. Data were collected in three waves from 288 participants through an online data collection platform in China. The results indicated that employee narcissism negatively predicts organizational commitment, and this process is mediated by perceived supervisor support. We also discuss the moderating role of abusive supervisors on perceived supervisor support, confirming that external self-value threat affects perceived support of narcissistic individuals. These results contribute to our understanding of the role of narcissism in organizations.